Intelligent building halogen-free heat-insulating fireproof cable and preparation method thereof

CN121583619BActive Publication Date: 2026-10-20江苏渠成电缆科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511659185.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2026-10-20
Estimated Expiration
2045-11-13

AI Technical Summary

Technical Problem

[0003]目前市场上具有防火性能的电缆主要分为三类,一种是玻璃丝布带粘合云母片缠绕在铜线外表面作为防火层,该电缆防火性能差,产品的防火温度及耐火时间无法到达现代高层建筑的设计规范,同时外层的玻璃丝在高温时防火性能较差;另一种是使用矿物质粉末作为绝缘层的硬性防火电缆,该电缆外层为铜管,铺设硬性防火电缆,工艺复杂,生产难度大,生产及使用成本较高,弯曲性能较差,安装及施工比较困难;最后一种是硅橡胶绝缘电缆,硅橡胶防火温度低,因此防火性能较差,发生火灾会释放出有毒气体

Benefits of technology

(1)本申请提出导体采用多根超细镀镍软铜丝进行蜂窝式分层绞合的方式,能使丝与丝之间的空隙最小化,绞合更紧密,内部应力能够沿着绞合层均匀地重新分布,避免了应力集中于几根丝上,从而极大地延缓了金属疲劳的发生;并分阶段对绞合缝隙填充导电胶、阻水胶,上述方式制备的电缆在智能建筑的安装中能够轻松通过弯角、桥架,并且在长期运行中能耐受轻微的振动,极大地避免了因反复弯曲或安装应力集中导致的内部结构损伤,从而保证了其抗屈挠性,进一步保障了防火性能的长期可靠性;还可以形成最佳的弹性缓冲和导电通路,并提供最高等级的纵向阻水保证,为智能建筑中可能存在的潮湿环境或意外浸水风险提供保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121583619B_ABST
    Figure CN121583619B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of refractory materials, in particular to a halogen-free heat-insulating fireproof cable for intelligent buildings and a preparation method thereof. The halogen-free heat-insulating fireproof cable for intelligent buildings comprises, from inside to outside, an insulated cable core, a metal heat transfer layer, a fireproof functional layer and a sheath layer. The preparation method comprises the following steps: S1, preparing the insulated cable core; S2, coating the metal heat transfer layer; S3, preparing the fireproof functional layer; and S4, sheath layer extrusion coating. The cable prepared by the application can easily pass through the corner and the bridge in the installation of the intelligent building, and can tolerate slight vibration in long-term operation, so that internal structure damage caused by repeated bending or installation stress concentration is greatly avoided, the flex resistance is ensured, and the long-term reliability of the fireproof performance is further ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory materials technology, specifically to a halogen-free heat-insulating fireproof cable for intelligent buildings and its preparation method. Background Technology

[0002] Halogen-free insulated cables are cables that combine flame retardancy, low smoke, and halogen-free properties. They are mainly used to reduce the release of smoke and toxic gases during fires, slow the spread of fire, and ensure the safety of personnel and the operation of equipment.

[0003] Currently, fire-resistant cables on the market are mainly divided into three categories. One type uses glass fiber tape bonded with mica sheets wrapped around the outer surface of copper wire as a fireproof layer. This type of cable has poor fire resistance, and its fire resistance temperature and fire resistance time cannot meet the design specifications for modern high-rise buildings. In addition, the outer glass fiber layer has poor fire resistance at high temperatures. Another type is a rigid fire-resistant cable that uses mineral powder as the insulation layer. This type of cable has a copper tube as the outer layer and is laid with rigid fire resistance. The process is complex, difficult to produce, and has high production and usage costs. It also has poor bending performance and is difficult to install and construct. The last type is silicone rubber insulated cable. Silicone rubber has a low fire resistance temperature, so its fire resistance is poor, and it will release toxic gases in the event of a fire.

[0004] Cables in smart buildings need to be frequently connected to new equipment or have their lines adjusted, which requires a certain level of resistance to repeated bending. For applications in smart buildings, cables may need to pass through cable trays and conduits and bend at junction boxes. Therefore, excellent flexural strength is an important indicator to ensure convenient installation and long-term reliable operation. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a halogen-free heat-insulating fireproof cable for intelligent buildings and its preparation method.

[0006] The technical solution of the present invention is: a halogen-free heat-insulating fireproof cable for intelligent buildings, which consists of an insulated cable core, a metal heat transfer layer, a fireproof functional layer and a sheath layer from the inside out; The insulated cable core consists of a conductor and a fire-resistant insulating sleeve wrapped around the conductor; the conductor is composed of multiple nickel-plated soft copper wires with a diameter of 0.15-0.25mm, twisted in a honeycomb pattern; the weight ratio of the fire-resistant insulating sleeve to the conductor is 3-5:2; the multiple fine wires twisted together are more flexible than a single thick conductor, allowing the cable to be bent repeatedly without metal fatigue fracture, and the layered twisting further optimizes the stress distribution; The metal heat transfer layer is a spirally arranged soft aluminum or copper strip with a thickness of 0.1-0.15mm and a spiral pitch of 3-5mm. When the cable is bent, the spiral pitch can naturally stretch or compress, which greatly releases the bending stress and avoids the wrinkling or flattening problems that are prone to occur when rigid metal tubes are bent. The fireproof functional layer consists of a mineral oxygen barrier layer with a thickness of 1.2-1.8 mm, a halogen-free heat insulation layer with a thickness of 0.8-1.2 mm, and a metal fire-resistant layer with a single-layer strip thickness of 0.05-0.15 mm, from the inside out. The mineral oxygen barrier layer, by weight percentage, includes: 15-25 wt% magnesium oxide powder, 8-12 wt% wollastonite powder, 25-35 wt% sodium silicate, 20-30 wt% calcined kaolin, and the balance perlite powder. The halogen-free heat insulation layer is fiberglass cloth coated with flame-retardant paint, and the metal fire-resistant layer is tin-plated copper strip. The calcined kaolin is arranged in parallel overlapping layers in the coating to form a multi-layered dense structure, which not only effectively blocks heat and oxygen but also improves the density, strength, and toughness of the coating, making it less prone to cracking when the cable is bent. The sheath layer has a thickness of 1.5-2.0 mm and is composed of 85-100 parts by weight of halogen-free flame-retardant polyolefin material, 5-15 parts by weight of flexural composite additive, and 10-20 parts by weight of flexibility agent.

[0007] Furthermore, the honeycomb layered stranding method is as follows: 1-3 first nickel-plated soft copper wires are placed in parallel as the inner core layer; Then, 6-8 second nickel-plated soft copper wires with a diameter of 22-28% of the first nickel-plated soft copper wire are twisted counterclockwise around the outer periphery of the inner core layer. The twisting pitch is controlled at 8-10 times the diameter of the inner core layer to form an intermediate layer. Conductive adhesive accounting for 1.5-3.0% of the total weight of the inner core layer and the intermediate layer is filled into the gap between the intermediate layer and the inner core layer. Next, 10-12 third nickel-plated soft copper wires with a diameter of 115-125% of the second nickel-plated soft copper wire are twisted clockwise around the outer periphery of the intermediate layer, with the twisting pitch controlled at 8-10 times the diameter of the intermediate layer, forming the outermost layer. The gap between the intermediate layer and the outermost layer is filled with hot-melt water-blocking adhesive accounting for 3.5-5.5% of the total weight of the intermediate layer and the outermost layer. Finally, the conductor is subjected to scanning tempering treatment with a fiber laser under a protective atmosphere to obtain the stranded conductor. Note: When the conductive adhesive is added in the above amounts, it ensures that the contact points are covered, forming optimal elastic buffer and conductive path, achieving the best resistance to flexural deformation. When the water-blocking adhesive is added in the above amounts, it forms a high-performance, uniformly thick sealing film, providing the highest level of longitudinal water resistance, and protecting against potential damp environments or accidental water immersion risks in smart buildings.

[0008] Furthermore, the conductive adhesive is a flexible silicone resin filled with 75-85 wt% silver powder or copper powder, and the hot-melt water-blocking adhesive is a mixture of hydrogenated styrene-butadiene block copolymer and polyester yarn with sodium polyacrylate externally adhered, in a mass ratio of 100:30-50. Note: Silver or copper powder provides stable conductivity, while the flexible silicone matrix ensures that the colloid does not become brittle when bent. While fixing the conductor, it enhances interlayer conductivity and reduces skin effect and proximity effect losses in high-frequency signal transmission, playing an important role in protecting high-speed data cables in intelligent buildings. Water-blocking adhesive can expand rapidly when exposed to water, sealing gaps and providing excellent longitudinal water-blocking performance.

[0009] Further, the preparation method of the polyester yarn with sodium polyacrylate externally adhered is as follows: water-based polyurethane, sodium polyacrylate powder, and deionized water are mixed in a mass ratio of 1:1-3:0.8-1.5 to obtain an impregnation solution; the surface of the polyester yarn is cleaned, and then plasma-treated for 60-180s under conditions of 300-500W power, 30-100Pa pressure, and 20-30℃ temperature; then the plasma-treated yarn is guided through an impregnation tank containing the impregnation solution, and vibrated by an ultrasonic transducer with a frequency of 35-45kHz and a power density of 0.3-0.6 W / cm² until the yarn is completely impregnated; finally, the impregnated wet yarn is dried in an electric heating drying oven at 80-120℃ for 25-35min to obtain the polyester yarn with sodium polyacrylate externally adhered. Explanation: Low-temperature plasma pretreatment of yarn can greatly improve the polarity of the polyester yarn surface, increase its surface energy and roughness, thereby significantly improving the wettability and adhesion of the subsequent coating liquid; the cavitation effect and intense vibration generated by ultrasound can keep the sodium polyacrylate powder in a uniform suspension state in the liquid, preventing sedimentation, and also helps the impregnation liquid penetrate into the tiny gaps in the yarn fibers, ensuring that the functional powder is uniformly attached to both the inner and outer surfaces of the yarn, greatly increasing the adhesion area and uniformity; this makes the sodium polyacrylate firmly adhered to the yarn, and even if it absorbs water and swells, it will be constrained and supported by the high-strength polyester yarn, better maintaining the overall shape and structural integrity of the colloid, providing durable and reliable water-blocking ability.

[0010] Furthermore, the parameters of the scanning tempering process are as follows: target temperature is 200-220℃, laser power is 800-1200W, scanning speed is 5-15m / min, spot diameter is 3-6mm, scanning path is helical scanning, and protective atmosphere is nitrogen. Note: Passing in a small amount of inert gas can prevent the copper wire from slightly oxidizing at high temperatures, keeping the nickel plating layer bright. The target temperature for the copper wire is below the recrystallization temperature, which can effectively eliminate internal stress without changing the grain structure. For the colloid, it can further promote cross-linking and curing, and optimize elasticity.

[0011] Furthermore, the fire-resistant insulating sleeve is made of ceramicized fire-resistant silicone rubber. Note: The ceramicized fire-resistant silicone rubber material is flexible at room temperature, but can be "ceramized" at high temperatures under flame to form a hard, ceramic-like protective shell that provides insulation and heat protection, thus achieving an effective fireproof effect.

[0012] Furthermore, the flexural strength composite additive is a compound composed of methyl vinyl silicone rubber and silane coupling agent in a mass ratio of 100:5-15; the flexibility agent is a polyolefin elastomer. Explanation: Methyl vinyl silicone rubber is renowned for its excellent high and low temperature resistance, superior flexibility, elasticity, and fatigue resistance. Introducing it as an additive into the outer sheath matrix significantly improves the sheath material's resistance to repeated bending and its resilience. Polyolefin elastomers make the cable surface smoother, facilitating cable pulling in cable trays and conduits while reducing surface wear caused by friction. Silane coupling agents improve the compatibility between flame-retardant fillers and polyolefins, as well as the compatibility between silicone rubber and polyolefins, preventing additive agglomeration and ensuring uniform and stable performance; facilitating installation in complex passageways of intelligent buildings.

[0013] This application also provides a method for preparing a halogen-free heat-insulated fire-resistant cable for intelligent buildings, comprising the following steps: S1. Preparation of insulated cable core The conductor is preheated to 80-100℃, and then a layer of ceramicized refractory silicone rubber containing 0.8-1.2wt% vulcanization accelerator is coated on the surface of the conductor. The conductor is then vulcanized in saturated steam at 180-220℃ for 3-5 minutes to obtain the insulated cable core. The vulcanization accelerator is 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. S2, Metal heat transfer layer A soft aluminum or copper strip is spirally wrapped around the outside of the insulated cable core to obtain a metal heat transfer layer. S3. Preparation of fire-resistant functional layer S3-1, Mineral Oxygen Barrier Coating Magnesium oxide powder, wollastonite powder, calcined kaolin and perlite powder are mixed at a speed of 20-40 rpm for 15-20 minutes. Then sodium silicate is added and the speed is adjusted to 40-60 rpm. Mixing continues for 30-45 minutes to obtain a paste. The paste is then extruded and coated onto the outside of the metal heat transfer layer using an extrusion coating machine to form a coating layer. The coating layer is then cured at a temperature of 100-120℃ for 20-30 minutes to obtain a mineral oxygen barrier layer. S3-2, Halogen-free insulation layer coating On the surface of the mineral oxygen barrier layer, the glass fiber cloth coated with flame retardant paint is wrapped in three overlapping layers in the right-left-right direction with an overlap rate of 50-60% to form a halogen-free heat insulation layer. The three overlapping layers allow for interface slippage between the layers. When the cable is bent, slight slippage between the wrapping layers is allowed, thus avoiding the complete concentration of bending stress on a single point. S3-3, Metal fire-resistant layer coating On the surface of the halogen-free insulation layer, the material of the metal fire barrier layer is wrapped in two layers with an overlap rate of 70-80% to form the metal fire barrier layer. S4, Sheath layer extrusion S4-1, Preparation of sheath material Halogen-free flame-retardant polyolefin material, accounting for 1 / 3 to 2 / 3 of the total amount of halogen-free flame-retardant polyolefin material, and flexural composite additives are added to a mixer with a speed of 300-500 rpm and mixed for 5-8 minutes. Then, the mixture is melt-blended and granulated through a first twin-screw extruder to obtain the first sheath material granules. Then, the remaining halogen-free flame-retardant polyolefin material, the flexibility agent, and the first sheath material granules are added to a mixer with a speed of 800-1200 rpm and mixed for 5-8 minutes. The mixture is then melt-blended and granulated through a second twin-screw extruder to obtain the second sheath material granules. S4-2, Sheath Extrusion The second sheath material granules are fed into an extruder and extruded onto the outermost layer of the cable at a temperature of 150-170℃ to form a continuous and smooth sheath with a thickness of 1.5-2.0mm. The sheath is then water-cooled and shaped to obtain the halogen-free heat-insulated fireproof cable for intelligent buildings. Explanation: Compared with granular fillers, calcined kaolin paste used in mineral oxygen barrier paste can form a stronger mechanical interlocking effect, which greatly enhances the adhesion between the oxygen barrier layer and the metal layer. When the cable is repeatedly bent, the maximum stress is concentrated at the interface of different materials. The strong interface bonding of the sheet filler can effectively prevent the oxygen barrier layer from peeling off from the metal layer, reduce fireproof structure failure and performance degradation, and thus improve flexural strength. The limited overlap of the halogen-free insulation layer facilitates the construction of a dense and resilient insulation barrier, effectively blocking heat transfer inward. Its layered structure also absorbs stress through interlayer slippage when the cable is bent, improving overall flexibility. The fire-resistant layer adopts a large overlap to ensure the continuity and integrity of the metal fire-resistant layer, effectively reflecting heat radiation and reducing flame impact in the early stages of a fire. At the same time, its interstitial structure retains the cable's flexibility. The two-step preparation of sheath material particles can improve the cable surface quality, long-term flame retardant stability, and enhance the cable's resistance to flexural stress cracking.

[0014] Furthermore, in S4-1, the processing temperature of the first twin-screw extruder is 140-160℃, the screw speed is 200-300rpm, and the extrusion time is 20-50s; the processing temperature of the second twin-screw extruder is 150-170℃, the screw speed is 250-350rpm, and the extrusion time is 10-40s. Explanation: The lower rotation speed in the first stage provides a gentle shear field, which can effectively break up the additive clumps and distribute them initially and evenly in part of the base material; the second stage ensures that the components are fully mixed by increasing the temperature and speed, thereby making the flexibility agent evenly distributed and the sheath material particles relatively stable, thus ensuring the flexural strength and flexibility of the sheath material.

[0015] Furthermore, in S4-2, the water cooling process involves cooling for 30-40 seconds in an environment with a water temperature of 15-25°C. Note: This design reduces the shrinkage rate of the sheath, which is beneficial for forming a tight interface bond with the inner layer.

[0016] Compared with existing technologies, the beneficial effects of this invention are: (1) This application proposes that the conductor adopts a honeycomb layered stranding method using multiple ultra-fine nickel-plated soft copper wires, which can minimize the gap between the wires, make the stranding tighter, and redistribute the internal stress evenly along the stranded layer, avoiding stress concentration on a few wires, thereby greatly delaying the occurrence of metal fatigue; and fill the stranded gaps with conductive glue and water-blocking glue in stages. The cable prepared in the above manner can easily pass through bends and cable trays during the installation of intelligent buildings, and can withstand slight vibrations during long-term operation, greatly avoiding internal structural damage caused by repeated bending or installation stress concentration, thereby ensuring its flexural strength and further ensuring the long-term reliability of fire resistance; it can also form the best elastic buffer and conductive path, and provide the highest level of longitudinal water-blocking guarantee, providing protection against the possible humid environment or accidental water immersion risk in intelligent buildings.

[0017] (2) The mineral oxygen barrier layer of this application introduces a high proportion of calcined kaolin, which makes full use of the parallel overlapping arrangement of calcined kaolin in the coating to form a multi-layered dense structure. This not only effectively blocks heat and oxygen, but also improves the density, strength and toughness of the coating, making the coating less prone to cracking when the cable is bent. This not only meets the fire protection requirements, but also significantly improves the toughness and bending crack resistance of the inorganic coating, transforming it from a brittle material into a tough material. This avoids the oxygen barrier layer itself from pulverizing and cracking when bent, thus losing its fire protection function and ensuring the fire protection reliability of the flexible structure. Attached Figure Description

[0018] Figure 1 This is a comparison chart of the performance of cables prepared in Examples 1-18 and Comparative Examples 1-6 of the present invention; Figure 2 This is a comparison chart of the cable performance prepared in Examples 1 / 2, 19-24 and Comparative Examples 7-8 of the present invention; Figure 3 This is a comparison chart of the cable performance prepared in Examples 1 / 2, Examples 25-36 and Comparative Example 9 of the present invention. Detailed Implementation

[0019] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.

[0020] Example 1: A halogen-free heat-insulated fireproof cable for intelligent buildings, consisting of an insulated core, a metal heat transfer layer, a fireproof functional layer, and a sheath layer from the inside out; The insulated cable core consists of a conductor and a fire-resistant insulating sleeve wrapped around the conductor; the conductor is composed of multiple nickel-plated soft copper wires with a diameter of 0.2mm twisted together in a honeycomb pattern; the weight ratio of the fire-resistant insulating sleeve to the conductor is 2:1. The honeycomb layered stranding method is as follows: two first nickel-plated soft copper wires are placed in parallel as the inner core layer; Then, seven second nickel-plated soft copper wires with a diameter of 25% of the first nickel-plated soft copper wire are twisted counterclockwise around the outer periphery of the inner core layer. The twisting pitch is controlled at 9 times the diameter of the inner core layer to form an intermediate layer. The gap between the intermediate layer and the inner core layer is filled with conductive adhesive accounting for 2.2% of the total weight of the inner core layer and the intermediate layer. The conductive adhesive is a flexible silicone resin filled with 80wt% silver powder. Next, 11 third nickel-plated soft copper wires with a diameter of 120% of the second nickel-plated soft copper wire are clockwise twisted around the outer periphery of the intermediate layer, with the twisting pitch controlled at 9 times the diameter of the intermediate layer, forming the outermost layer. A hot-melt water-blocking adhesive, accounting for 4.5% of the total weight of the intermediate and outermost layers, is then filled into the gap between the intermediate and outermost layers. Finally, a scanning tempering process is performed using a fiber laser under a protective atmosphere to obtain the stranded conductor. The hot-melt water-blocking adhesive is a mixture of hydrogenated styrene-butadiene block copolymer and polyester yarn with externally adhered sodium polyacrylate in a mass ratio of 10:4. The parameters for the scanning tempering process are: target temperature 210℃, laser power 1000W, scanning speed 10m / min, spot diameter 4mm, scanning path spiral scanning, and protective atmosphere nitrogen. The preparation method of polyester yarn with sodium polyacrylate externally adhered is as follows: water-based polyurethane, sodium polyacrylate powder, and deionized water are mixed at a mass ratio of 1:2:1 to obtain an impregnation solution; the surface of the polyester yarn is cleaned, and then plasma-treated for 120s under the conditions of 400W power, 60Pa air pressure, and 25℃ temperature; then the plasma-treated yarn is guided through an impregnation tank containing the impregnation solution, and vibrated by an ultrasonic transducer with a frequency of 40kHz and a power density of 0.5 W / cm² until the yarn is completely impregnated; finally, the impregnated wet yarn is dried in an electric heating drying oven at 100℃ for 30min to obtain polyester yarn with sodium polyacrylate externally adhered. The fire-resistant insulation sleeve is made of ceramicized fire-resistant silicone rubber. The metal heat transfer layer is a spirally arranged soft aluminum strip with a thickness of 0.13 mm and a spiral spacing of 4 mm; The mineral oxygen barrier layer is 1.6 mm thick and, by weight percentage, includes: 20 wt% magnesium oxide powder, 10 wt% wollastonite powder, 30 wt% sodium silicate, 25 wt% calcined kaolin and the balance perlite powder. The halogen-free insulation layer is made of three layers of fiberglass cloth coated with flame-retardant paint, with a thickness of 1.0 mm. The metal fire-resistant layer is a double-layered tin-plated copper strip, with a single layer thickness of 0.10mm; The sheath layer is 1.8 mm thick and consists of 92 parts by weight of halogen-free flame-retardant polyolefin material, 10 parts by weight of flexural composite additive and 15 parts by weight of flexible agent. The flexural strength additive is a compound composed of methyl vinyl silicone rubber and silane coupling agent in a mass ratio of 10:1; the flexibility agent is a polyolefin elastomer.

[0021] Example 2: A method for preparing a halogen-free heat-insulated fireproof cable for intelligent buildings based on Example 1, comprising the following steps: S1. Preparation of insulated cable core The conductor is preheated to 90°C, and then a layer of ceramicized refractory silicone rubber containing 1.0 wt% vulcanization accelerator is coated on the surface of the conductor. The conductor is then vulcanized in saturated steam at 200°C for 4 min to obtain the insulated cable core. The vulcanization accelerator is 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. S2, Metal heat transfer layer A soft aluminum strip is spirally wrapped around the outside of the insulated cable core to obtain a metal heat transfer layer. S3. Preparation of fire-resistant functional layer S3-1, Mineral Oxygen Barrier Coating Magnesium oxide powder, wollastonite powder, calcined kaolin and perlite powder are mixed and mixed at 30 rpm for 18 minutes. Then sodium silicate is added and the speed is adjusted to 50 rpm. Mixing continues for 38 minutes to obtain a paste. The paste is then extruded and coated onto the outside of the metal heat transfer layer using an extrusion coating machine to form a coating. The coating is then cured at 110°C for 25 minutes to obtain a mineral oxygen barrier layer. S3-2, Halogen-free insulation layer coating On the surface of the mineral oxygen barrier layer, the glass fiber cloth coated with flame retardant paint is wrapped in three layers in a right-left-right direction with a 55% overlap rate to form a halogen-free heat insulation layer. S3-3, Metal fire-resistant layer coating On the surface of the halogen-free insulation layer, the material of the metal fire barrier layer is wrapped in two layers with an overlap rate of 75% to form a metal fire barrier layer. S4, Sheath layer extrusion S4-1, Preparation of sheath material Half of the total amount of halogen-free flame-retardant polyolefin material and flexural composite additives were added to a mixer with a speed of 400 rpm and mixed for 7 minutes. Then, the mixture was melt-blended and granulated through a first twin-screw extruder at a temperature of 150℃, a screw speed of 250 rpm, and an extrusion time of 20-50 seconds to obtain the first sheath material granules. Then, the remaining halogen-free flame-retardant polyolefin material, the flexible agent, and the first sheath material granules were added to a mixer with a speed of 1000 rpm and mixed for 7 minutes. The mixture was then melt-blended and granulated through a second twin-screw extruder at a temperature of 160°C, a screw speed of 300 rpm, and an extrusion time of 22 seconds to obtain the second sheath material granules. S4-2, Sheath Extrusion The second sheath material granules are fed into an extruder and extruded onto the outermost layer of the cable at a temperature of 160°C to form a continuous and smooth sheath with a thickness of 1.8mm. The sheath is then water-cooled for 35 seconds at a water temperature of 20°C to obtain a halogen-free heat-insulated fireproof cable for intelligent buildings.

[0022] Example 3: Unlike Example 1, six second nickel-plated soft copper wires with a diameter of 22% of the first nickel-plated soft copper wire are then twisted counterclockwise around the outer periphery of the inner core layer. The twisting pitch is controlled at 8 times the diameter of the inner core layer to form an intermediate layer. Conductive adhesive accounting for 1.5% of the total weight of the inner core layer and the intermediate layer is then filled into the gap between the intermediate layer and the inner core layer.

[0023] Example 4: Unlike Example 1, eight second nickel-plated soft copper wires with a diameter of 28% of the first nickel-plated soft copper wire are then twisted counterclockwise around the outer periphery of the inner core layer. The twisting pitch is controlled at 10 times the diameter of the inner core layer to form an intermediate layer. Conductive adhesive accounting for 3.0% of the total weight of the inner core layer and the intermediate layer is then filled into the gap between the intermediate layer and the inner core layer.

[0024] Example 5: Unlike Example 1, the conductive adhesive is a flexible silicone resin filled with 75 wt% silver powder.

[0025] Example 6: Unlike Example 1, the conductive adhesive is a flexible silicone resin filled with 85 wt% silver powder.

[0026] Example 7: Unlike Example 1, 10 third nickel-plated soft copper wires with a diameter of 115% of the second nickel-plated soft copper wire are then twisted clockwise around the outer periphery of the intermediate layer, and hot-melt water-blocking adhesive accounting for 3.5% of the total weight of the intermediate and outermost layers is filled into the gap between the intermediate layer and the outermost layer to form the outermost layer.

[0027] Example 8: Unlike Example 1, 12 third nickel-plated soft copper wires with a diameter of 125% of the second nickel-plated soft copper wire are then twisted clockwise around the outer periphery of the intermediate layer, and hot-melt water-blocking adhesive accounting for 5.5% of the total weight of the intermediate and outermost layers is filled into the gap between the intermediate layer and the outermost layer to form the outermost layer.

[0028] Example 9: Unlike Example 1, the hot-melt water-blocking adhesive is a mixture of hydrogenated styrene-butadiene block copolymer and polyester yarn with sodium polyacrylate externally adhered, in a mass ratio of 10:3.

[0029] Example 10: Unlike Example 1, the hot-melt water-blocking adhesive is a mixture of hydrogenated styrene-butadiene block copolymer and polyester yarn with sodium polyacrylate externally adhered, in a mass ratio of 10:1.

[0030] Example 11: Unlike Example 1, the method for preparing polyester yarn with sodium polyacrylate adhering to the outside is as follows: waterborne polyurethane, sodium polyacrylate powder and deionized water are mixed in a mass ratio of 1:1:0.8 to obtain an impregnation solution; the surface of the polyester yarn is cleaned, and then plasma treated for 60s under the conditions of 300W power, 30Pa pressure and 20℃ temperature.

[0031] Example 12: Unlike Example 1, the method for preparing polyester yarn with sodium polyacrylate adhering to the outside is as follows: water-based polyurethane, sodium polyacrylate powder and deionized water are mixed in a mass ratio of 2:6:3 to obtain an impregnation solution; the surface of the polyester yarn is cleaned, and then plasma treated for 180s under the conditions of 500W power, 100Pa pressure and 30℃. Example 13: Unlike Example 1, the plasma-treated yarn was then guided through a sizing tank containing sizing solution and vibrated with an ultrasonic transducer at a frequency of 35 kHz and a power density of 0.3 W / cm² until the yarn was completely sizing. Finally, the sizing wet yarn was dried in an electric heating drying oven at 80°C for 25 minutes to obtain polyester yarn with sodium polyacrylate adhering to the outside.

[0032] Example 14: Unlike Example 1, the plasma-treated yarn was then guided through a sizing tank containing sizing solution and vibrated with an ultrasonic transducer at a frequency of 45 kHz and a power density of 0.6 W / cm² until the yarn was completely sizing. Finally, the sizing wet yarn was dried in an electric heating drying oven at 120°C for 35 minutes to obtain polyester yarn with sodium polyacrylate adhering to the outside.

[0033] Example 15: Unlike Example 1, the parameters for the scanning tempering process are: target temperature of 200℃, laser power of 800W, scanning speed of 5m / min, and spot diameter of 3mm.

[0034] Example 16: Unlike Example 1, the parameters for the scanning tempering process are: target temperature of 220℃, laser power of 1200W, scanning speed of 15m / min, and spot diameter of 6mm.

[0035] Example 17: Unlike Example 1, the metal heat transfer layer is a spirally arranged soft aluminum strip with a thickness of 0.1 mm and a spiral spacing of 3 mm.

[0036] Example 18: Unlike Example 1, the metal heat transfer layer is a spirally arranged soft aluminum strip with a thickness of 0.15 mm and a spiral spacing of 5 mm.

[0037] Example 19: Unlike Example 1, the mineral oxygen barrier layer is 1.2 mm thick and, by mass percentage, includes: 15 wt% magnesium oxide powder, 8 wt% wollastonite powder, 25 wt% sodium silicate, 20 wt% calcined kaolin and the balance perlite powder.

[0038] Example 20: Unlike Example 1, the mineral oxygen barrier layer is 1.8 mm thick and, by mass percentage, includes: 25 wt% magnesium oxide powder, 12 wt% wollastonite powder, 35 wt% sodium silicate, 30 wt% calcined kaolin and the balance perlite powder.

[0039] Example 21: Unlike Example 1, the sheath layer has a thickness of 1.5 mm and is composed of 85 parts by weight of halogen-free flame-retardant polyolefin material, 5 parts by weight of flexural composite additive and 10 parts by weight of flexible agent.

[0040] Example 22: Unlike Example 1, the sheath layer has a thickness of 2.0 mm and is composed of 100 parts by weight of halogen-free flame-retardant polyolefin material, 15 parts by weight of flexural composite additive and 20 parts by weight of flexible agent.

[0041] Example 23: Unlike Example 1, the flexural strength composite additive is a compound composed of methyl vinyl silicone rubber and silane coupling agent in a mass ratio of 20:1.

[0042] Example 24: Unlike Example 1, the flexural strength composite additive is a compound composed of methyl vinyl silicone rubber and silane coupling agent in a mass ratio of 20:3.

[0043] Example 25: Unlike Example 2, in S1, the conductor is preheated to 80°C, and then a layer of ceramicized refractory silicone rubber containing 0.8wt% vulcanization accelerator is coated on the surface of the conductor, and vulcanized in saturated steam at 180°C for 3 minutes to obtain an insulated cable core.

[0044] Example 26: Unlike Example 2, in S1, the conductor is preheated to 100°C, and then a layer of ceramicized refractory silicone rubber containing 1.2 wt% vulcanization accelerator is coated on the surface of the conductor, and vulcanized in saturated steam at 220°C for 5 minutes to obtain an insulated cable core.

[0045] Example 27: Unlike Example 2, in S3-1, magnesium oxide powder, wollastonite powder, calcined kaolin and perlite powder are mixed and mixed at 20 rpm for 15 min. Then sodium silicate is added and the speed is adjusted to 40 rpm. Mixing continues for 30 min to obtain a paste. The paste is then extruded and coated onto the outside of the metal heat transfer layer using an extrusion coating machine to form a coating layer. The coating layer is then cured at 100°C for 20 min to obtain a mineral oxygen barrier layer.

[0046] Example 28: Unlike Example 2, in S3-1, magnesium oxide powder, wollastonite powder, calcined kaolin and perlite powder are mixed and mixed at 40 rpm for 20 min. Then sodium silicate is added and the speed is adjusted to 60 rpm. Mixing continues for 45 min to obtain a paste. The paste is then extruded and coated onto the outside of the metal heat transfer layer using an extrusion coating machine to form a coating layer. The coating layer is then cured at 120°C for 30 min to obtain a mineral oxygen barrier layer.

[0047] Example 29: Unlike Example 2, in S3-2, on the surface of the mineral oxygen barrier layer, the glass fiber cloth coated with flame retardant coating is wrapped in three layers in a right-left-right direction with a 50% overlap rate to form a halogen-free heat insulation layer.

[0048] Example 30: Unlike Example 2, in S3-2, on the surface of the mineral oxygen barrier layer, the glass fiber cloth coated with flame retardant coating is wrapped in three layers in a right-left-right direction with a 60% overlap rate to form a halogen-free heat insulation layer.

[0049] Example 31: Unlike Example 2, in S3-3, the material of the metal fire barrier layer is wrapped in two layers with a 70% overlap rate on the surface of the halogen-free heat insulation layer to form a metal fire barrier layer.

[0050] Example 32: Unlike Example 2, in S3-3, the metal fire barrier material is double-wrapped on the surface of the halogen-free heat insulation layer with an 80% overlap rate to form a metal fire barrier layer.

[0051] Example 33: Unlike Example 2, in S4-1, halogen-free flame-retardant polyolefin base material accounting for 1 / 3 of the total amount of halogen-free flame-retardant polyolefin base material and flexural composite additive are added to a mixer with a speed of 300 rpm and mixed for 5 minutes. Then, under the conditions of a temperature of 140°C, a screw speed of 200 rpm and an extrusion time of 20 seconds, the mixture is melt-blended and granulated through a first twin-screw extruder to obtain the first sheath material particles. Then, the remaining halogen-free flame-retardant polyolefin base material, the flexibility agent, and the first sheath material granules were added to a mixer with a speed of 8000 rpm and mixed for 5 minutes. The mixture was then melt-blended and granulated through a second twin-screw extruder at a temperature of 150°C, a screw speed of 250 rpm, and an extrusion time of 15 seconds to obtain the second sheath material granules.

[0052] Example 34: Unlike Example 2, in S4-1, halogen-free flame-retardant polyolefin base material accounting for 2 / 3 of the total amount of halogen-free flame-retardant polyolefin base material and flexural composite additive are added to a mixer with a speed of 500 rpm and mixed for 8 minutes. Then, under the conditions of temperature of 160°C, screw speed of 300 rpm and extrusion time of 50 seconds, it is melt-blended and granulated through a first twin-screw extruder to obtain the first sheath material particles. Then, the remaining halogen-free flame-retardant polyolefin base material, the flexibility agent, and the first sheath material granules were added to a mixer with a speed of 1200 rpm and mixed for 8 minutes. The mixture was then melt-blended and granulated through a second twin-screw extruder at a temperature of 170°C, a screw speed of 350 rpm, and an extrusion time of 40 seconds to obtain the second sheath material granules.

[0053] Example 35: Unlike Example 2, in S4-2, the second sheath material particles are fed into an extruder and extruded onto the outermost layer of the cable at a temperature of 150°C to form a continuous and smooth sheath with a thickness of 1.5mm. The sheath is then cooled and shaped in a water environment at a water temperature of 15°C for 30 seconds to obtain a halogen-free heat-insulated fireproof cable for intelligent buildings.

[0054] Example 36: Unlike Example 2, in S4-2, the second sheath material particles are fed into an extruder and extruded onto the outermost layer of the cable at a temperature of 170°C to form a continuous and smooth sheath with a thickness of 2.0 mm. The sheath is then cooled and shaped in a water environment at a water temperature of 25°C for 40 seconds to obtain a halogen-free heat-insulated fireproof cable for intelligent buildings.

[0055] Experimental Example: The description of this experimental example is based on the scheme described in Examples 1 / 2, and aims to illustrate the practical application effect of the present invention.

[0056] 1. Experimental Design: To elucidate the flexural strength, fire resistance, and water resistance of the halogen-free heat-insulating fire-resistant cable prepared according to this invention, the following experimental group was designed: The method for determining the flexural fatigue cycles is as follows: refer to GB / T 13934-1992 "Determination of Flexural Cracking of Vulcanized Rubber"; Fire resistance test: Fire resistance performance shall be tested in accordance with the requirements and methods of GB / T2406.2-2009, and the initial oxygen index shall be recorded; the higher the oxygen index, the better the fire resistance performance. Water resistance test: Cables were prepared using the methods of Examples 1-32 and Comparative Examples 1-7, respectively. The initial tensile strength was tested and the data were recorded. The cables were then completely immersed in water for 48 hours. After the cables were removed, the tensile strength after immersion was tested again using a computerized tensile tester (purchased from Jinan Alpha Electronic Equipment Co., Ltd., model XLW-PC). The data were recorded and the tensile strength retention rate was calculated. The higher the tensile strength retention rate, the better the water resistance and water resistance of the cable sheath material. 1. Investigating the impact of honeycomb layered stranding method on the performance of halogen-free heat-insulated fire-resistant cables for intelligent buildings. Comparative Example 1: Unlike Example 1, the nickel-plated soft copper wire has a uniform diameter.

[0057] Comparative Example 2: Unlike Example 1, the flexible silicone resin was replaced with polyurethane resin.

[0058] Comparative Example 3: Unlike Example 1, all stranding is performed in the same direction.

[0059] Comparative Example 4: Unlike Example 1, sodium polyacrylate powder was directly mixed with hydrogenated styrene-butadiene block copolymer in the hot melt water-blocking adhesive.

[0060] Comparative Example 5: Unlike Example 1, the polyester yarn was not subjected to plasma treatment.

[0061] Comparative Example 6: Unlike Example 1, the step of ultrasonic transducer vibration is missing.

[0062] Conclusion: A comparison of Examples 1-4 and Comparative Example 1 shows that the lack of limitation on the diameter of the nickel-plated soft copper wire in Comparative Example 1 leads to a decrease in the performance of the halogen-free heat-insulating fire-resistant cable. This is because the design of Example 1, with its thinner inner layer wires, even thinner middle layer wires, and thicker outer layer wires, allows for better stress transition and dispersion during conductor bending, preventing stress concentration in a single layer and significantly delaying fatigue fracture. In contrast, the use of copper wires of the same diameter in Comparative Example 1 results in the outer copper wires bearing the greatest tensile strain and the inner wires bearing compressive strain during cable bending, easily leading to stress concentration. In the process of bending, the copper wires break more quickly; and when wires of the same diameter are twisted together, the gaps between the layers are large, and the structure is not dense enough. During repeated bending, the internal copper wires will scrape and wear against each other, accelerating fatigue. Furthermore, because there are gaps between nickel-plated soft copper wires of the same diameter, the water-blocking adhesive filling is easily unevenly distributed, which weakens the barrier effect against water vapor penetration, resulting in a more significant decrease in tensile strength and thus a lower tensile strength retention rate. Since the fire resistance of the cable mainly depends on the structure of the ceramicized silicone rubber insulation layer, mineral oxygen barrier layer, and metal fireproof layer, the structure of the cable core has a relatively small impact on the fire resistance effect. Comparison of Examples 1 / 2, Examples 5-6, and Comparative Example 2 shows that replacing flexible silicone resin with polyurethane resin is a good choice. Although polyurethane resin has excellent flexibility and elasticity, which can maintain the integrity of the conductive path when the conductive adhesive is bent, its heat resistance is poor. The heat generated when the conductor is working may cause it to age, thereby affecting the flexural life. In addition, due to the flammable nature of polyurethane, it may produce toxic gases when burning, which seriously violates the principle of halogen-free flame retardancy and will significantly reduce the fire safety of the cable. Therefore, flexible silicone resin is the best choice. A comparison of Examples 1, 3-4, 7-8 and Comparative Example 3 shows that the concentrated internal stress generated by the co-directional stranding in Comparative Example 3 causes the single filaments in the conductor to bear additional torsional stress, which greatly accelerates metal fatigue and leads to a sharp decrease in flexural life. Furthermore, co-directional stranding easily causes uneven distribution of the conductive and water-blocking adhesives filled inside, providing a potential channel for the longitudinal penetration of water vapor, weakening the overall water-blocking barrier effect of the conductor, resulting in a reduction in the tensile strength retention rate. In addition, the twisting method of the conductor will also transfer stress to other external structural layers, which may cause relative displacement or even damage to these layers, affecting the fireproof effect. A comparison of Examples 1 / 2, Examples 9-10, and Comparative Example 4 shows that directly mixing sodium polyacrylate powder with hydrogenated styrene-butadiene block copolymer in hot-melt water-blocking adhesives also leads to a decrease in cable performance. This is because sodium polyacrylate swells after absorbing water and becomes a soft hydrogel. If it is only loosely distributed in the hydrogenated styrene-butadiene block copolymer, the structural strength of the entire composite adhesive will decrease significantly after absorbing water, and it may be dispersed by water pressure, losing its water-blocking effect. However, adhering sodium polyacrylate powder to polyester yarn can utilize the high-strength polyester yarn for constraint and support, better maintaining the overall shape and structural integrity of the adhesive, providing durable and reliable water-blocking capability, and thus ensuring the long-life flexural strength of the cable. A comparison of Examples 1 / 2, Examples 11-12 and Comparative Example 5 shows that the lack of a plasma treatment step can lead to a decrease in cable performance. This is because low-temperature plasma pretreatment of yarn can effectively increase the polarity of the polyester yarn surface, increase its surface energy and roughness, thereby significantly improving the wettability and adhesion of the subsequent coating liquid, strengthening the bond between sodium polyacrylate and polyester yarn, improving the water-blocking effect, and further optimizing the cable's flexural strength. A comparison of Examples 1 / 2, Examples 13-14, and Comparative Example 6 shows that the lack of ultrasonic transducer vibration leads to a decrease in cable performance. This is because the cavitation effect and intense vibration generated by ultrasound can keep the sodium polyacrylate powder in a uniform suspension state in the liquid, preventing sedimentation. It also helps the impregnation solution penetrate into the tiny gaps in the fibers inside the yarn, ensuring that the functional powder can be uniformly attached to both the inner and outer surfaces of the yarn. This greatly increases the attachment area and uniformity, further improving water resistance, thereby ensuring the stability of the internal environment of the cable and optimizing its flexural strength.

[0063] 2. Investigate the influence of the composition of the mineral oxygen barrier layer and the sheath layer on the performance of halogen-free heat-insulated fireproof cables for intelligent buildings. Comparative Example 7: Unlike Example 1, calcined kaolin was replaced with mica.

[0064] Comparative Example 8: Unlike Example 1, the flexural composite additive does not contain a silane coupling agent.

[0065] Conclusion: A comparison of Examples 1 / 2, Examples 19-20, and Comparative Example 7 shows that although both calcined kaolin and mica are sheet-like structures, under bending stress, mica sheets are less prone to elastic deformation than calcined kaolin, which can lead to increased coating brittleness. Furthermore, the bonding force between mica and the silica base is relatively limited, and poor interfacial bonding can result in low stress transfer efficiency and easy cracking of the coating at the filler interface. This affects the various performance characteristics of halogen-free heat-insulated fireproof cables for intelligent buildings.

[0066] By comparing Examples 1 / 2, Examples 23-24, and Comparative Example 8, it can be seen that during the extrusion process of the sheath, since the glass fiber cloth of the halogen-free heat insulation layer is also a silicate material that is easily bonded by silane coupling agents, part of the silane coupling agent can penetrate into the mineral oxygen barrier layer, while the other part remains in the sheath as a component of the flexural additive. This satisfies both the need to improve the flexibility of the sheath and the need to improve the interfacial bonding ability of the coating. Therefore, the flexural additive component proposed in this application also has a good improvement effect.

[0067] 3. Investigate the impact of the preparation method of halogen-free heat-insulated fire-resistant cables for intelligent buildings on their performance. Comparative Example 9: Unlike Example 2, in S4-1, the raw materials are directly mixed to obtain the sheath material.

[0068] Conclusion: A comparison of Examples 2, 33-34, and Comparative Example 9 shows that the cable performance of the sheath material obtained by directly mixing the raw materials in S4-1 is lower than that of the step-by-step mixing method of this application. This is because the two-step method for preparing the sheath material particles allows for the pre-dispersion and surface wetting of the flexural composite additive using a portion of the halogen-free flame-retardant polyolefin base material. Then, the addition of the flexibility agent and the remaining halogen-free flame-retardant polyolefin base material, along with further mixing with the first sheath material, results in a more uniform and stable bond between the flexural additive and the matrix resin, and allows for more complete penetration of the flexibility agent. The sheath material is incorporated into the polymer network, resulting in excellent uniformity and processing flowability of the sheath particles. This allows for better coating of the complex outer layer of the cable, improving the surface quality, long-term flame retardant stability, and enhancing the cable's resistance to flexural stress and water resistance. In contrast, the sheath material directly mixed in Comparative Example 9 cannot achieve uniform dispersion at the nanoscale or microscale in the matrix under limited shear force and time. When the cable is bent or subjected to environmental stress, cracks will preferentially propagate from these weak points, leading to a sharp decline in resistance to flexural stress and water resistance, thereby weakening the overall performance of the cable.

Claims

1. A halogen-free, heat-insulated, fire-resistant cable for intelligent buildings, characterized in that, From the inside out, the layers are: insulated cable core, metal heat transfer layer, fireproof functional layer, and sheath layer. The insulated cable core consists of a conductor and a fire-resistant insulating sleeve wrapped around the conductor; the conductor is composed of multiple nickel-plated soft copper wires stranded in layers; the inner core layer of the stranded core is composed of a first nickel-plated soft copper wire with a diameter of 0.15-0.25mm; the weight ratio of the fire-resistant insulating sleeve to the conductor is 3-5:

2. The layered stranding method is as follows: 1-3 first nickel-plated soft copper wires are placed as the inner core layer; Then, 6-8 second nickel-plated soft copper wires with a diameter of 22-28% of the first nickel-plated soft copper wire are twisted counterclockwise around the outer periphery of the inner core layer. The twisting pitch is controlled at 8-10 times the diameter of the inner core layer to form an intermediate layer. Conductive adhesive accounting for 1.5-3.0% of the total weight of the inner core layer and the intermediate layer is filled into the gap between the intermediate layer and the inner core layer. Next, 10-12 third nickel-plated soft copper wires with a diameter of 115-125% of the second nickel-plated soft copper wire are twisted clockwise around the outer periphery of the intermediate layer, with the twisting pitch controlled at 8-10 times the diameter of the intermediate layer, forming the outermost layer. The gap between the intermediate layer and the outermost layer is filled with hot-melt water-blocking adhesive accounting for 3.5-5.5% of the total weight of the intermediate layer and the outermost layer. Finally, the conductor is subjected to scanning tempering treatment with a fiber laser under a protective atmosphere to obtain the stranded conductor. The metal heat transfer layer is a spirally arranged soft aluminum or copper strip with a thickness of 0.1-0.15 mm and a spiral spacing of 3-5 mm. The fireproof functional layer consists of a mineral oxygen barrier layer with a thickness of 1.2-1.8mm, a halogen-free heat insulation layer with a thickness of 0.8-1.2mm, and a metal fire-resistant layer with a single-layer strip thickness of 0.05-0.15mm, from the inside out. The mineral oxygen barrier layer comprises, by weight percentage: 15-25 wt% magnesium oxide powder, 8-12 wt% wollastonite powder, 25-35 wt% sodium silicate, 20-30 wt% calcined kaolin and the balance perlite powder; the halogen-free heat insulation layer is fiberglass cloth coated with flame-retardant paint, and the metal fireproof layer is tin-plated copper strip. The sheath layer has a thickness of 1.5-2.0 mm and is composed of 85-100 parts by weight of halogen-free flame-retardant polyolefin material, 5-15 parts by weight of flexural composite additive, and 10-20 parts by weight of flexibility agent.

2. The halogen-free heat-insulated fireproof cable for intelligent buildings as described in claim 1, characterized in that, The conductive adhesive is a flexible silicone resin filled with 75-85 wt% silver or copper powder, and the hot-melt water-blocking adhesive is a mixture of hydrogenated styrene-butadiene block copolymer and polyester yarn with sodium polyacrylate externally adhered, in a mass ratio of 100:30-50.

3. The halogen-free heat-insulated fireproof cable for intelligent buildings as described in claim 2, characterized in that, The method for preparing the polyester yarn with sodium polyacrylate externally adhered is as follows: Waterborne polyurethane, sodium polyacrylate powder, and deionized water are mixed at a mass ratio of 1:1-3:0.8-1.5 to obtain an impregnation solution; the surface of the polyester yarn is cleaned, and then plasma-treated for 60-180 seconds under conditions of 300-500W power, 30-100Pa pressure, and 20-30℃ temperature; subsequently, the plasma-treated yarn is guided through an impregnation tank containing the impregnation solution, supplemented by a frequency of 35-45kHz and a power density of 0.3-0.6 W / cm². 2 The ultrasonic transducer vibrates until the yarn is completely soaked. Finally, the soaked wet yarn is dried in an electric heating drying oven at 80-120℃ for 25-35 minutes to obtain polyester yarn with sodium polyacrylate adhering to the outside.

4. The halogen-free heat-insulated fireproof cable for intelligent buildings as described in claim 1, characterized in that, The parameters for the scanning tempering process are as follows: target temperature 200-220℃, laser power 800-1200W, scanning speed 5-15m / min, spot diameter 3-6mm, scanning path is helical scanning, and protective atmosphere is nitrogen.

5. The halogen-free heat-insulated fireproof cable for intelligent buildings as described in claim 1, characterized in that, The fire-resistant insulating sleeve is made of ceramicized fire-resistant silicone rubber.

6. The halogen-free heat-insulated fireproof cable for intelligent buildings as described in claim 1, characterized in that, The flexural strength composite additive is a compound composed of methyl vinyl silicone rubber and silane coupling agent in a mass ratio of 100:5-15; the flexibility agent is a polyolefin elastomer.

7. A method for preparing a halogen-free heat-insulated fire-resistant cable for intelligent buildings as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of insulated cable core The conductor is preheated to 80-100℃, then a layer of fire-resistant insulating material is wrapped around the surface of the conductor, and vulcanized in saturated steam at 180-220℃ for 3-5 minutes to obtain the insulated cable core. S2, Metal heat transfer layer A soft aluminum or copper strip is spirally wrapped around the outside of the insulated cable core to obtain a metal heat transfer layer. S3. Preparation of fire-resistant functional layer S3-1, Mineral Oxygen Barrier Coating Magnesium oxide powder, wollastonite powder, calcined kaolin and perlite powder are mixed at a speed of 20-40 rpm for 15-20 minutes. Then sodium silicate is added and the speed is adjusted to 40-60 rpm. Mixing continues for 30-45 minutes to obtain a paste. The paste is then extruded and coated onto the outside of the metal heat transfer layer using an extrusion coating machine to form a coating layer. The coating layer is then cured at a temperature of 100-120℃ for 20-30 minutes to obtain a mineral oxygen barrier layer. S3-2, Halogen-free insulation layer coating On the surface of the mineral oxygen barrier layer, the glass fiber cloth coated with flame retardant paint is wrapped in three layers in a right-left-right direction with an overlap rate of 50-60% to form a halogen-free heat insulation layer. S3-3, Metal fire-resistant layer coating On the surface of the halogen-free insulation layer, the material of the metal fire barrier layer is wrapped in two layers with an overlap rate of 70-80% to form the metal fire barrier layer. S4, Sheath layer extrusion S4-1, Preparation of sheath material Halogen-free flame-retardant polyolefin material, accounting for 1 / 3 to 2 / 3 of the total amount of halogen-free flame-retardant polyolefin material, and flexural composite additives are added to a mixer with a speed of 300-500 rpm and mixed for 5-8 minutes. Then, the mixture is melt-blended and granulated through a first twin-screw extruder to obtain the first sheath material granules. Then, the remaining halogen-free flame-retardant polyolefin material, the flexibility agent, and the first sheath material granules are added to a mixer with a speed of 800-1200 rpm and mixed for 5-8 minutes. The mixture is then melt-blended and granulated through a second twin-screw extruder to obtain the second sheath material granules. S4-2, Sheath Extrusion The second sheath material granules are fed into an extruder and extruded onto the outermost layer of the cable at a temperature of 150-170℃ to form a continuous and smooth sheath with a thickness of 1.5-2.0mm. The sheath is then water-cooled and shaped to obtain the halogen-free heat-insulated fireproof cable for intelligent buildings.

8. The method for preparing a halogen-free heat-insulated fire-resistant cable for intelligent buildings as described in claim 7, characterized in that, In S4-1, the processing temperature of the first twin-screw extruder is 140-160℃, the screw speed is 200-300rpm, and the extrusion time is 20-50s; the processing temperature of the second twin-screw extruder is 150-170℃, the screw speed is 250-350rpm, and the extrusion time is 15-40s.

9. The method for preparing a halogen-free heat-insulated fire-resistant cable for intelligent buildings as described in claim 7, characterized in that, In S4-2, the water-cooling shaping is performed by cooling for 30-40 seconds in an environment with a water temperature of 15-25℃.

Citation Information

Patent Citations

  • Unequal diameter round single line composite twisted layer conductor

    CN101051536A

  • Flexible mineral insulated cable and manufacturing process thereof

    CN115331877A